2014
DOI: 10.3390/catal4030256
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity of Mono- and Bi-Metallic Nanoparticles Synthesized via Microemulsions

Abstract: Water-in-oil (w/o) microemulsions were used as a template for the synthesis of mono-and bi-metallic nanoparticles. For that purpose, w/o-microemulsions containing H 2 PtCl 6 , H 2 PtCl 6 + Pb(NO 3 ) 2 and H 2 PtCl 6 + Bi(NO) 3 , respectively, were mixed with a w/o-microemulsion containing the reducing agent, NaBH 4 . The results revealed that it is possible to synthesize Pt, PtPb and PtBi nanoparticles of ~3-8 nm in diameter at temperatures of about 30°C. The catalytic properties of the bimetallic PtBi and PtP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 36 publications
(68 reference statements)
1
21
0
Order By: Relevance
“…A more flexible surfactant film allows a faster material exchange [101] and, as a result, the difference between reduction rates is minimized, giving rise to a higher degree of mix [72]. This outcome can be clearly established from Table 1, by focusing our attention on nanoparticles prepared using a very flexible film, such as in a water/CTAB/isooctane/n-butanol microemulsion (see experiments number 15,25,28). All…”
Section: Keeping the Pair Of Metals Fixedmentioning
confidence: 93%
See 1 more Smart Citation
“…A more flexible surfactant film allows a faster material exchange [101] and, as a result, the difference between reduction rates is minimized, giving rise to a higher degree of mix [72]. This outcome can be clearly established from Table 1, by focusing our attention on nanoparticles prepared using a very flexible film, such as in a water/CTAB/isooctane/n-butanol microemulsion (see experiments number 15,25,28). All…”
Section: Keeping the Pair Of Metals Fixedmentioning
confidence: 93%
“…The presence of a second metal in a bimetallic nanoparticle not only reduces the cost as some noble metal that is substituted by a non-noble one, but also modifies the interactions between atoms giving rise to changes in the structure and surface. The electron interactions between two metal atoms, which are electron-rich, just as the heterometallic bonding interactions change the surface electronic properties of the nanoparticles [12][13][14][15][16][17][18][19]. As a rule, the catalytic behaviour is usually enhanced on bimetallic nanoparticles as compared to monometallic nanoparticles [3,7,[13][14][15][17][18][19][20][21] even at low Rai et al [46] suggest that the synergic cooperation between the two metals is more noticeable in alloyed nanoparticles, due to the higher probability of metal-metal interactions in comparison to core-shell ones.…”
Section: Bimetallic Nanoparticles As Catalystsmentioning
confidence: 99%
“…A synthesis procedure based on water-in-oil ME for mono (Pt) and bimetallic (PtBi, PtPb) nanoparticles is reported in the article by König et al [29]; furthermore, the catalytic activity was also reported [17]. As the authors concluded, bimetallic nanoparticles could be obtained, which consist of a mixture of different phases; the composition of the bimetallic particles was varied as a function of the metal salt ratio and the amount of reducing agent.…”
Section: The Present Issuementioning
confidence: 99%
“…Apart from biological conversion, p ‐NP can be oxidized via chemical treatment with oxidizing agents such as hydrogen peroxide or ozone among others. Anaerobic biological degradation or catalytic reduction (eg, with the use of nanoparticles) leads in general to formation of 4‐aminophenol . Aqueous photolysis of nitrophenols by solar ultraviolet (UV) radiation proceeding via radical formation results in release of nitro group in the form of nitrous acid …”
Section: Introductionmentioning
confidence: 99%